Visible-to-near-infrared light-harvesting A-π-D-π-A porphyrins for boosted photocatalytic hydrogen evolution. Issue 3 (4th January 2023) - Bodedla, Govardhana Babu; Piradi, Venkatesh; Imran, Muhammad; Zhao, Jianzhang; Zhu, Xunjin; Wong, Wai-Yeung
Abstract : Visible-to-near-infrared light-harvesting A-π-D-π-A porphyrins, ZnP-CPDT and ZnP-BT are proved to be highly efficient in photocatalytic hydrogen evolution (PHE) with the highest PHE rate ( η H2 ) of 1.80 mmol g −1 h −1 for ZnP-CPDT . Abstract : Developing visible-to-near-infrared light-harvesting porphyrin photosensitizers is very important for efficient photocatalytic hydrogen evolution (PHE) since most of the tetra- meso -substituted porphyrins absorb up to the visible region only. Herein, two new A-π-D-π-A porphyrins ZnP-CPDT and ZnP-BT containing a meso -2, 6-dodecyloxyphenyl substituted porphyrin donor (D) moiety, cyclopentadithiophene (CPDT)/bithiophene (BT)-ethynylene π-linkers, and a 3-ethylrhodanine acceptor (A) group are synthesized and characterized by UV-vis absorption, photoluminescence, and morphological, density functional theoretical (DFT) and PHE studies. The two porphyrins are capable of absorbing in the region of 370 to 800 nm in solution and 300 to 1100 nm in the solid state indicating their visible-to-near-infrared light-harvesting ability. The Soret- and Q-band absorption peaks of ZnP-CPDT with a CPDT linker are more red-shifted than those of ZnP-BT containing a BT linker due to the enhanced intramolecular charge transfer (ICT) between the porphyrin donor and 3-ethylrhodanine acceptor moieties. Moreover, better photoinduced charge separation was observed for ZnP-CPDT than ZnP-BT as manifested by the photocurrent-time studies. Noteworthily, a well-defined nanosphere morphology was observed for ZnP-CPDT, while agglomerated morphology was found for ZnP-BT in the solid-state. As a consequence, the ZnP-CPDT porphyrin produced a PHE rate ( η H2 ) of 1.80 mmol g −1 h −1 which is 4.5-fold higher than that of the ZnP-BT porphyrin (0.40 mmol g −1 h −1 ). Under the same photocatalytic conditions, the typical zinc(ii )-tetraphenylporphyrin (ZnTPP ) which absorbs visible light, delivered a very low η H2 of 0.05 mmol g −1 h −1 . The higher η H2 of ZnP-CPDT than that of ZnP-BT is attributed to the efficient light harvesting in the visible-to-near-infrared region, facile photoinduced charge separation and well-defined nanosphere morphology, resulting in improved electron transfer from the photoexcited porphyrin moiety to the Pt cocatalyst for proton reduction. Moreover, the superior PHE performance of both ZnP-CPDT and ZnP-BT porphyrins compared to that of ZnTPP is mainly ascribed to the visible-to-near-infrared light-harvesting ability and efficient photoinduced charge separation. This work helps to develop efficient A-π-D-π-A-based porphyrins for PHE by suitable molecular design.